Retrofitting Approaches for Office Buildings in Tropical Climates: A Systematic Review - Bencid, Mariana; Chung-Camargo, Katherine; Chen Austin, Miguel (LACCEI, 2024)
The alarming energy crisis developing worldwide has driven investigation towards minimizing the impact of the energy sector on the global emissions of greenhouse gases (GHG). As the building sector represents 30% of global energy consumption, efforts must be made to address the increasing energy demand in buildings, especially existing buildings, since they currently represent the majority of energy consumed in the sector. In this study, a bibliometric analysis was conducted to identify research opportunities based on a literature review of energy efficiency strategies applied to existing office buildings in the tropics with the objective of analyzing the most efficient retrofit measures under this type of climate. The analysis showed little available investigation on buildings in tropical climates, especially involving office buildings. Results showed that the most studied passive strategies were related to the glazing component of the envelope, including using low-emissivity materials, semi-transparent photovoltaic modules, or electrochromic materials. However, active strategies such as efficient HVAC systems have been demonstrated to achieve higher reductions in the electrical consumption of the building when compared to passive strategies.